Intraoperative release of troponin T in coronary venous and arterial blood and its relation to recovery of left ventricular function and oxidative metabolism following coronary artery surgery. Issue 4 (1st October 1998) - Koh, T W; Hooper, J; Kemp, M; Ferdinand, F D; Gibson, D G; Pepper, J R
Abstract : Objective: To investigate the intraoperative release of troponin T during uncomplicated coronary artery surgery and to determine its relation to ischaemic time and to recovery of left ventricular function and oxidative metabolism. Design: A prospective observational study. Setting: Cardiac surgical unit in a tertiary referral centre. Methods: Troponin T, creatine kinase, and lactate were analysed from arterial and coronary sinus samples taken before operation, and 1, 4, 6, 10, 20, 35, and 45 minutes after cross clamp release. Net myocardial troponin T release and lactate extraction were derived from their respective arteriovenous differences. Haemodynamic measurements were made using a thermodilution pulmonary artery catheter. Patients: 45 patients, mean (SD) age 62 (9) years, with two or three vessel coronary artery disease and chronic stable angina undergoing routine coronary artery surgery. Results: Before operation, troponin T concentrations were not raised, but within one minute of cross clamp release they increased progressively in both coronary sinus and arterial blood for the entire 45 minutes of reperfusion studied. Coronary sinus troponin T concentrations were consistently higher than arterial concentrations at all time points (p < 0.001), indicating net troponin T release by the myocardium. Peak net troponin T release and area under the curve of net troponin T release correlated closely with ischaemic time ( r = 0.58 and r = 0.61, p < 0.0001 for both). Area under the curve of arterial troponin T concentration was also significantly correlated with ischaemic time ( r = 0.44, p < 0.01). Patients with cross clamp times longer than 72 minutes (upper quartile for ischaemic time) had greater troponin T release, delayed reversion to lactate extraction, and lower left ventricular stroke work index three hours after surgery, compared with patients who had short (< 50 minutes, lower quartile) and intermediate (51–71 minutes, interquartile) cross clamp times. Peak net troponin T release and area under the curve of arterial troponin T concentration were inversely correlated with left ventricular stroke work index three hours after surgery ( r = −0.57, r = −0.38, p < 0.01). Conclusions: Troponin T concentrations increased in every patient after cross clamp release, and were consistently higher in coronary sinus blood than in arterial blood, indicating net myocardial release of troponin T during the period of reperfusion. Intraoperative net troponin T release has functional significance, as it is closely related to ischaemic time and reflects delayed recovery of left ventricular function and oxidative metabolism; therefore, its measurement may contribute to the perioperative assessment of myocardial injury sustained during coronary artery surgery.